'On being the right size'2 – Do aliens follow the rules?. (11th January 2018) - van der Geer, Alexandra A.E.; Lomolino, Mark V.; Lyras, George
Abstract: Aim: To assess whether mammalian species introduced onto islands across the globe have evolved to exhibit body size patterns consistent with the 'island rule, ', and to test an ecological explanation for body size evolution of insular mammals. Location: Islands worldwide. Methods: We assembled data on body mass, geographical characteristics (latitude, maximum elevation) and ecological communities (number of mammalian competitors, predators and prey) for 385 introduced populations across 285 islands, comprising 56 species of extant, non‐volant mammals. We used linear regression, ANCOVA and regression tree analyses to test whether introduced populations of mammals exhibit the island rule pattern, whether the degree of body size change increased with time in isolation and whether residual variation about the general trend can be attributed to the geographical and ecological characteristics of the islands. Results: Introduced populations follow the predicted island rule trend, with body size shifts more pronounced for populations with greater residence times on the islands. Small mammals evolved to larger body sizes in lower latitudes and on islands with limited topographic relief. Consistent with our hypothesis on the ecology of evolution, body size of insular introduced populations was influenced by co‐occurring species of mammalian competitors, predators and prey. Conclusion: The island rule is a pervasive pattern, exhibited across a broad span of geographical regions, taxa, time periods and, as evidenced here, for introduced as well as native mammals. Time in isolation impacts body size evolution profoundly. Body size shift of introduced mammals was much more pronounced with increasing residence times, yet far less than that exhibited by native, palaeo‐insular mammals (residence times > 10, 000 years). Given the antiquity of many species introductions, it appears that much of what we view as the natural character and ecological dynamics of recent insular communities may have been rendered artefacts of ancient colonizations by humans and commensals.